Functional PET imaging in cancer drug development. (April 2007) - Avril, Norbert; Propper, David
New surrogate end points for monitoring response to cancer treatment are needed for both current and novel therapeutic strategies. Positron emission tomography (PET) as a functional imaging technology provides rapid, reproducible, noninvasive in vivo assessment and quantification of several biological processes targeted by anticancer therapies. PET imaging with F-18 fluorodeoxyglucose (FDG), reflecting tumor glucose metabolism, provides relevant information regarding treatment response. Changes in tumor glucose metabolism precede changes in tumor size and reflect drug effects at a cellular level. FDG-PET enables the prediction of therapy response early in the course as well as determining the viability of residual masses after completion of treatment. The assessment of novel anticancer agents will increasingly depend on functional PET imaging. Assessing responses to new biological drugs using changes in tumor size is likely an inaccurate measure of efficacy. Likewise, monitoring for drug effects using surrogate (nontumor) tissues or serial invasive testing by tumor biopsies does not provide a good correlation with overall antitumor activity. Therefore, the information derived from PET using radiolabeled biological probes provides an alternative approach to conventional structural (anatomical) imaging. PET pharmacokinetic studies will allow for the rapid assessment of novel drug biodistribution, and much smaller patient number studies before decisions on whether or not to proceed with the development of a new drug are made. Summative readouts by PET, such as drug-induced changes in tumor glucose metabolism, tumor cell proliferation and tumor perfusion and, similarly, measures of specific changes will demonstrate whether drugs are having their intended biological effects.